Multiple Retained Ocular Bee Stingers - Arti Sareen; Mukta Sharma; S. S. Negi (Delhi Journal of Ophthalmology)
Bee sting injuries, though rare in the eye, can be visually incapacitating for the patient if they occur. They have a wide variety of ocular manifestations ranging from involvement of the ocular surface right up to the optic nerve. This could be due to the venom of the bee itself, the sharp nature of the stinger, the toxic nature of the singer or the induction of the immunological response by the patient. Also, the introduction of the stinger in the eye may sometimes cause infection. These can individually or in part play a role in the clinical manifestations of a patient. We report a case of a 24-year-old female who had history of anaphylaxis due to multiple bee stings all over her body (including severe periorbital edema) one month back. After resolution of her acute symptoms she noticed a foreign body sensation, redness, lacrimation diminution of vision and pain in her left eye for which she came to us. Her Visual Acuity at presentation was 6/12in the left eye. On slit lamp examination two stingers were found embedded in her upper tarsal conjunctiva and one stinger was seen in the anterior chamber. All the three stingers were successfully removed mechanically after which she was prescribed topical antibiotics, steroids and cyclopentolate. This led to resolution of all her symptoms and improvement of her visual acuity to 6/6 within 5 days.